2012
DOI: 10.1159/000335496
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis and Risk of Venous Thromboembolism: A Population-Based Cohort Study

Abstract: Background: Multiple sclerosis (MS) patients may be at increased risk of venous thromboembolism (VTE), but evidence is limited. Objectives: To examine long-term risk of VTE among MS patients. Patients and Methods: We conducted a population-based cohort study among 17,418 Danish MS patients and 87,090 comparison cohort members from the general population. Data on MS, VTE and comorbidities were obtained from the Danish National Registry of Patients including all admissions to Danish hospitals since 1977. We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
36
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 52 publications
6
36
0
2
Order By: Relevance
“…Our results are largely in agreement with those reported in recent epidemiological studies. A recent Danish study by Christensen et al . found a roughly 2‐fold increase in the occurrence rate of DVT and PE in MS patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our results are largely in agreement with those reported in recent epidemiological studies. A recent Danish study by Christensen et al . found a roughly 2‐fold increase in the occurrence rate of DVT and PE in MS patients.…”
Section: Discussionmentioning
confidence: 95%
“…Interpretation of the results of this initial study is, however, hindered by the lack of a description of the comparison group. In contrast, a recent Danish study reported an elevated risk of VTE associated with MS, with a 2‐ to 3‐fold increase in incidence rate among MS patients . However, this study lacked potentially important information on the presence of VTE risk factors (e.g.…”
Section: Introductionmentioning
confidence: 84%
“…In a large population-based cohort study evaluating data from a 30-year Danish National Registry, MS was associated with increased long-term risk of venous thromboembolism (11). Another paper, based on the review of one cohort study and three cross-sectional studies, found that early MS was associated with an increased risk of pulmonary embolism, deep venous thromboembolism, and stroke, both the latter persisting over time (12).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 An analysis of over 6000 patient deaths in the Danish National Registry of MS patients revealed that death by vascular or cardiac disease was the most frequently listed cause of death outside of MS itself. That is, ischaemic events are directly associated with irregular platelet functions and their prothrombotic activity.…”
mentioning
confidence: 99%